SISTEM INFORMASI GEOGRAFIS DISTRIBUSI SEMBAKO MURAH PADA BADAN URUSAN LOGISTIK (BULOG)KOTA GORONTALO - Farid Idham; Ruslin Nyungo (Jurnal Informatika Upgris, 2019)
Abstract - The problems encountered at Bulog Gorontalo city were a located to difficult find and knows seperate distribution rise done.The purpose of this study is to design a georafis information system to facilitate the public to gain access to information about the locations distribution rise status done or yet in the city of Gorontalo.Based on the test results by using test case proves that the geographic information system is more effective and efficient than the recording. Here is the conclusion of the test results V (G) = 6-6 + 2 = 2, V (G) = 1 + 1 = 2, Cyclomatic Complexity (CC) ie R1, R2 = 2.